Validity of RKS Model for New Product Launch - Shah, Kinnari; Srivastava, R. K. (Indian Journal of Marketing, 2005)
New products are the lifeblood of many companies. Indeed, many companies (such as 3M, Gillette, HP) set goals for sales based on new products. New products can be classified as ’Lemon-scented’ and ’really new products’. ’Lemon-scented’, slightly new products are relatively easy to forecast and low in risk and are often profitable. ’Really new products’, in contrast, are hard to forecast, take a long time to develop, and frequently produce profits for later entrants but not for pioneers. New product development shapes the company’s future. A Company can add new products through acquisition or development. The stakes are high in either case and millions of dollars are poured in the process. Hence managers the world over are constantly on the look out for ways and means that would minimise the risks associated and at the same time ensure the success of the new products. RKS model can be used as an effective tool to predict the success or failure of a product concept. It clearly indicates how good is a product idea/concept.